Calcium hydroxylapatite treatment of human skin: evidence of collagen turnover through picrosirius red staining and circularly polarized microscopy - Zerbinati N; Calligaro A (Dove Medical Press, 2018)
Nicola Zerbinati,1 Alberto Calligaro2 1Department of Surgical and Morphological Sciences, University of Insubria (Varese) and Polyspecialist Medical Center, Pavia, 2Department of Public Health, Experimental and Forensic Medicine, Unit of Histology and Embryology, University of Pavia, Pavia, Italy Background: Calcium hydroxylapatite (CaHA, Radiesse®) is a biocompatible, injectable filler for facial soft-tissue augmentation that provides volume to tissues, followed by a process of neocollagenesis for improved skin quality. Objective: To examine the effects of CaHA treatment on the molecular organization of collagen using a combination of picrosirius red staining and circularly polarized light microscopy.Methods: Five subjects received subdermal injection of 0.3 mL of CaHA in tissues scheduled for removal during abdominoplasty 2 months later. Tissue specimens from the CaHA injection site and a control untreated area were obtained from excised skin at the time of surgery. Processed tissue sections were stained with picrosirius red solution 0.1% and visualized under circularly polarized light microscopy for identification of thick mature (type I) and thin newly formed (type III) collagen fibers. Pixel signals from both the control and CaHA-treated areas were extracted from the images, and morphometric computerized hue analysis was performed to provide a quantitative evaluation of mature and newly formed collagen fibers.Results: Under picrosirius red staining and circularly polarized light microscopy, green/yellow areas (thin newly formed collagen type III) were visible among the collagen fibers in tissue sections from the area of CaHA injection. In contrast, the majority of the collagen fibers appeared red (thick mature collagen type I) in control tissues. Morphometric analysis confirmed that, following CaHA treatment, the proportion of fibers represented by thin newly formed collagen type III increased significantly (p<0.01) in comparison with the proportion of thick mature collagen type I fibers. In contrast, collagen content of control tissues consisted almost exclusively of thick mature collagen type I fibers. Conclusion: The use of picrosirius red staining and circularly polarized light microscopy provides evidence that subdermal injection of CaHA stimulates the formation of new collagen and dermal remodeling. Keywords: calcium hydroxylapatite, neocollagenesis, picrosirius red, circularly polarized light microscopy, Radiesse